Nine genetic polymorphisms associated with power athlete status - A Meta-Analysis - Weyerstraß, J.; Stewart, K.; Wesselius, A.; Zeegers, M. (Journal of Science and Medicine in Sport, 2018)
Objectives: In this study the association between genetic polymorphisms and power athlete status with possible interference by race and sex was investigated to identify genetic variants favourable for becoming a power athlete. Design: This meta-analysis included both, case-control and Cohort studies. Methods: Databases of PubMed and Web of Science were searched for studies reporting on genetic polymorphisms associated with the status of being a power athlete. Thirty-five articles published between 2008 and 2016 were identified as eligible including a total number of 5834 power athletes and 14,018 controls. A series of meta-analyses were conducted for each of the identified genetic polymorphisms associated with power athlete status. Odds ratios (ORs) based on the allele and genotype frequency with corresponding 95% confidence intervals (95%CI) were calculated per genetic variant. Heterogeneity of the studies was addressed by Chi-square based Q-statistics at 5% significance level and a fixed or random effects model was used in absence or presence of heterogeneity respectively. Stratified analyses were conducted by race and sex to explore potential sources of heterogeneity. Results: Significant associations were found for the genetic polymorphisms in the ACE (rs4363, rs1799752), ACTN3 (rs1815739), AGT (rs699), IL6-174 (rs1800795), MnSOD (rs1799725), NOS3 (rs1799983, rs2070744) and SOD2 (rs4880) genes. Conclusions: Nine genetic polymorphisms have been identified in the meta-analyses to have a significant association with the status of being a power athlete. Nevertheless, more research on the investigated genes needs to be done to draw comprehensive conclusions.